(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
Exploration study was to identify leadership styles and cultural dispensation that support effective management in schools. Strategically the study looked at how effective leadership skills and cultural dispensation adopted informs effective leadership. Using Concurrent Triangulation Design under the descriptive survey design was employed to gather and analyse data in the context of qualitative and quantitative approach, data was collected using questionnaire, and semi structured interviews. Multi stage sampling techniques was used to. select three hundred and seven (307) participants that included (20) lecturers, (2) Principal/Vice principals, (285) Teacher-trainees and one (1) officer. Frequency tables, percentages, and person correlation statistical tool. Thematic analytical frame formed the qualitative data analysis. Respondents were ambivalent about their perception about the leadership styles, again respondents agreed that the culture of the college influences the leadership style adopted. Further, the findings of the study revealed that there was statistically significant difference in the lecturer’s leadership styles and their teaching experience. It was concluded that lecturers and students have varying views about use of leadership style/strategies within the college leadership, hence need for leaders to operate on same wavelength when it comes to use of leadership styles. It was therefore recommended that sensitization drive to help better understanding on use of leadership styles/strategies as well as versatility of school culture on leadership style/strategies of the SDA College of education.